Secagem de sementes de gramíneas (Brachiaria brizantha) em leito fluidizado - Rizzi Júnior, Antonio Carlos (Universidade Federal de São Carlos, 2008)
Drying operation is an important stage of the processing that precedes the storage of seeds, since that with low moisture contents, these can retain their power of germination and other qualities for long periods. The objective of this work was to perform a study of drying of grass seeds (Brachiaria brizantha) in a batch fluidized bed, in order to evaluate the performance of the dryer in a physiological and phenomenological point of view. Fluid dynamics, heat transfer and drying tests were accomplished in order to verify the operational limitations of the equipment, as well as determining the main characteristic experimental parameters of the seeds (such as minimum fluidization velocity and transfer coefficients). Moreover, two types of models were tested (three-phase and two-phase models) with the purpose of comparing the feasibility of its applications. Sensitivity analyses were carried out on the main parameters and properties of the models aiming to discuss their strengths and weaknesses. Besides, experimental comparisons of the drying process in the equipment operating as fixed bed and fluidized bed were made. Among the main results, it was found that the simplified two-phase model provided better predictions of the drying experiments in fluidized bed, specially the temperature of the bed, than the three-phase model, which takes into account the existence of the solid, interstitial gas and bubble gas phases. By applying the hypothesis test of equality between the experimental and simulated variables, it was found a P-value equal to 0,829 for the simplified model Tm variable, better than the three-phase model corresponding variables. The adopted drying kinetics represented well the process, which presented a correlation coefficient of 0,975 between the predicted and experimental data.
Keywords: Leito fluidizado; Secagem; Calor - transmissão; Modelo a três fases; Modelo a duas fases; ENGENHARIAS::ENGENHARIA QUIMICA